Chemical Fractions and Availability of Zinc in Winter Wheat Soil in Response to Nitrogen and Zinc Combinations - Liu, Hongen; Zhao, Peng; Qin, Shiyu; Nie, Zhaojun (Frontiers in Plant Science, 2018)
Nitrogen (N) is critical for zinc (Zn) accumulation in winter wheat grain via enhancing Zn absorption into plant roots. This paper explored a possible mechanism for enhanced absorption of Zn in winter wheat by N combined with Zn application based on the Zn bio-availability in soil. A pot experiment with three N application rates (0.05, 0.2 and 0.4 g kg-1), two Zn application rates (0 and 10 mg kg-1), without and with plants was conducted. The results showed that high N (N0.2 and N0.4) combined with Zn (Zn10) application significantly increased the yield, yield components and Zn and N concentrations in winter wheat shoots and grain. The available Zn concentration in soil with and without plants was increased by N0.2Zn10 and N0.4Zn10 treatment at each growth stage. N0.2Zn10 and N0.4Zn10 treatment significantly decreased the pH in soil without plants but had different influences on the pH in soil with plants, which depended on the different N application rates and growth stages. Meanwhile, N0.2Zn10 and N0.4Zn10 treatment decreased the exchangeable Zn but increased loose organic-, carbonate- and Fe-Mn oxides-bound Zn concentrations in soil without plants. The exchangeable, loose organic- and carbonate-bound Zn concentrations in soil with plants was increased by N0.2Zn10 and N0.4Zn10 treatment at different growth stages. Different rates of N combined with Zn application influenced the proportion of Zn in different fractions in soil with and without plants at different growth stages. At Zn10, N0.4 treatment showed higher yield, N and Zn concentrations in shoot and grain, and available Zn concentration in soil, but lower pH in soil than N0.2 treatment. In addition, soil without plants had higher available Zn concentrations and lower pH than did the soil with plants. There were significant differences in Zn chemical fractions concentrations and proportions between the soils with and without plants at each growth stage. Therefore, combined influence of roots and the combination of N and Zn (especially N0.4Zn10 treatment) improved the bio-availability of Zn in soil via changing the soil pH and promoting the transformation and distribution of Zn in different fractions.